Physico-chemical and functional properties of silver carp myosin glycated with konjac oligo-glucomannan: Effects of deacetylation. (1st September 2019) - Liu, Jianhua; Fang, Chunhua; Xu, Xia; Su, Qi; Zhao, Peicheng; Ding, Yuting
Highlights: The effects of deacetylation of KOG on the properties of myosin were studied. The available lysine content decreased, while the total sulfhydryl group increased. The isoelectric point shifted toward more acidic values. The solubility, thermal stability and emulsifying properties were increased. The removal of acetyl groups possibly facilitated the glycation. Abstract: The glycation of silver carp myosin (Ms) with konjac oligo-glucomannan (KOG) of different degrees of deacetylation (DD) was investigated. As DD increased, the physico-chemical and functional properties of glycoconjugates changed. The available lysine content decreased, while grafting degree and total sulfhydryl group increased, and meanwhile, the isoelectric point (p I ) reduced. SDS-PAGE analysis indicated that glycation can be promoted as the increase of DD. The solubility increased significantly both in 0.1 M and 0.5 M NaCl solution, and the thermal stability increased when heated for 60 min at 80 °C. The emulsifying activity index (EAI) and emulsifying stability index (ESI) increased as well. These results showed that the highly deacetylated KOG (DKOG) was easier to glycate with myosin, leading to a great improvement in functional properties of myosin. It can be suggested that the reduction in steric hindrance of DKOG as a result of removal of acetyl groups facilitated the glycation.